One-Year Results of an Algorithmic Approach to Managing Failed Back Surgery Syndrome - Martín Avellanal; Gonzalo Diaz-Reganon; Alejandro Orts; Silvia Soto (Pain Research and Management)
BACKGROUND: Failed back surgery syndrome (FBSS) is a major clinical problem. Different etiologies with different incidence rates have been proposed. There are currently no standards regarding the management of these patients. Epiduroscopy is an endoscopic technique that may play a role in the management of FBSS.